Etika Perdagangan dalam Perspektif Islam - Shafwatun Nada; Heni Ani Nuraeni (Jurnal Ilmiah Ekonomi Islam, 2023)
The research in this study focuses on a person's ethics in trading practices from an Islamic perspective. Ethics is an important thing to pay attention to in trading practices to maintain good relations between traders and buyers. Through this research, it is hoped that it can show how much Islam upholds ethics in various activities including in trading, where trade is carried out to seek sustenance and make ends meet. This study uses a descriptive-analytical method with literature from several sources, namely books, articles, and previous research results. The research conducted, it shows that Islamic ethics in trading practices have several principles, namely the principle of justice, the principle of free will, the principle of responsibility, and the principle of truth. One of the main things that are upheld in ethics in trading practices is to behave honestly. Honesty that is held by traders will create good socio-economic relations between traders and buyers so that no party is harmed in these trading practices.